Guinea : Third Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criterion and Financing Assurances Review-Press Release; Staff Report; Supplementary Information; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2019)
Guinea's strong growth momentum continues. Real growth is estimated at 5.8 percent in 2018 and expected at about 6 percent in 2019-20. The social context remains fragile. Social unrest, strikes and protests marred 2018. While strikes have subsided so far in 2019, political and social tensions are intensifying due to delays in the legislative elections and questions related to the 2020 presidential elections.